Mortalities in the neonatal unit: after-hours compared with normal working hours at Pelonomi Tertiary Hospital over a 1-year period (January 2017 to December 2017) - Duba, S. E. (University of the Free State, 2020)
Background: Neonatal mortality remains one of the leading causes of under-5-mortality in South Africa. South Africa has not reached the Millennium Development Goals targets for 2015 as set out by the WHO. The leading causes for neonatal mortality remains immaturity related (48.1%), complications of hypoxia (24.2%) and infections (11.2%). According to the PPIP and CHPIP program data, many of these deaths do have avoidable factors that are administrative and staff related. If there is a difference found in mortalities when comparing normal working hours with after-hours, then it is possible that administrative and staffing differences for these hours could be a reason for differences seen. This could assist relevant stakeholders to optimize allocation of resources (including staffing) as well as guide further research to investigate possible reasons for differences in mortalities for different time intervals. Objectives: This research set out to investigate whether or not there are differences in the number of neonatal mortalities at Pelonomi Tertiary Hospital, Bloemfontein, when comparing normal working hours with after-hours. If there are differences, then to determine if there are differences in the avoidable factors involved in these mortalities (according to the PPIP and CHPIP data). Method: This was a descriptive, cross-sectional study. The total number of mortalities (January 2017 – December 2017) for normal working hours and after-hours were investigated, and avoidable factors (according to PPIP and CHPIP codes) for these mortalities were compared. Results: A total number of 103 neonatal mortalities for this time period were included in this study. More deaths occurred after-hours (16:00 – 07:30 on weekday, whole weekends and whole public holidays) when compared to normal working hours (all other weekdays 07:30 – 16:00) (n=67, 65.05% vs n=36, 34.95%). When the time frames are divided into after-hours (any day 16:00 – 07:30) and normal working hours (any day 07:30 – 16:00), more deaths occurred after-hours (n=55, 53.4%). Most of these (any day) after-hour mortalities occurred between 16:00 and 00:00 (n=31, 56.4%). The most common causes of death for these neonates reflect the same causes as the national PPIP/CHPIP data, being 1. Infection related (n=26, 25.24%), 2. multi-organ immaturity (n=21, 20.39%) and 3.Complications of hypoxia (n=18, 17.48%). There were no major differences in administrative and staff-related avoidable factors when comparing these different time intervals. Conclusion: This study confirms that during this time period there were more neonatal deaths occurring after-hours when compared to normal working hours at Pelonomi Tertiary Hospital, Bloemfontein. Due to the design of this study we could not conclude whether or not these differences are statistically significant. To optimize allocation of limited resources and staffing, the researcher concludes that further research to determine the factors which may contribute to these differences in mortalities for different time intervals is warranted.
Dissertation (M.Med. (Paediatrics and Child Health))--University of the Free State, 2020
Keywords: Neonatal mortality; Normal working hours; Avoidable factors; Resource and staffing allocation; Infants -- South Africa -- Mortality; Neonatal mortality - After-hours; Neonatal mortality - Normal working hours